KONTEN REELS INSTAGRAM BIRO ADMINISTRASI PIMPINAN SEKRETARIAT DAERAH PEMERINTAHAN PROVINSI SUMATERA BARAT DALAM MEMBERIKAN INFORMASI YANG MENARIK KEPADA PUBLIK - Muhammad Raihan Fahri; Marhen Marhen (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The main problem in this study is that the many public responses regarding the use of social media in providing information made the Adpim Bureau of West Sumatra Province use social media Instagram reels for information media and packaged properly so that it becomes an interesting information medium for the community. The purpose of this study was to describe the use of instagram reels for the Administrative Bureau of the Regional Government Secretariat of West Sumatra Province in providing interesting public information. The type of research used is qualitative research with a descriptive approach. Data was collected through observation, interviews and documentation. Data analysis techniques were performed, namely data reduction (summarizing, choosing main points, focusing on important things, looking for themes and patterns), data presentation (brief descriptions/relationship charts between categories/flowcharts/and the like), and drawing conclusions. The technique of guaranteeing the validity of the data used is the triangulation technique. The results of the research conducted found that the first delivery of Instagram reels for public information begins with selecting a theme that is appropriate in the field or what actually happens besides that the Instagram reels content that is created also contains information for the Second, the use of Instagram reels for communication that appeals to the public is made as creatively as possible which aims to attract public interest and involve community participation in the content created. Apart from that, to make interesting content, Instagram reels are made containing issues that are happening and following current trends and collaborating with celebgrams and tiktokers. However, the quality of published videos is still not attractive to viewers because the quality presented is classified as blurry or not good.